Strategi Peningkatan Ketahanan Pangan Pada Masa Pandemic Covid-19 Di Dinas Ketahanan Pangan Kota Ternate Provinsi Maluku Utara: Strategy for Improving Food Security During the Covid-19 Pandemic at the Food Security Service, Ternate City, North Maluku Province - Indahsari, Mutiara; Ekaria, Ekaria; Muhammad, Munawir; Marsaoly, Hasrul A.; La Kamisi, Haryati (Jurnal Riset Agribisnis dan Peternakan, 2022)
Corona Virus Disease 2019 or commonly known as COVID-19 is an infectious disease caused by SARS-CoV-2, a type of corona virus. The City of Ternate is one of the areas that was also affected by COVID-19 in 2020. This study aims to analyze the situation of food security, analyze external and internal factors that affect food security and formulate strategies to improve food security in dealing with the COVID-19 pandemic in Ternate City . Primary data was obtained based on the results of surveys and interviews conducted by filling out questionnaires by selected respondents. Data sources that will be used later include internal data and external data. The formulation of strategies to increase food security uses Strategic Internal Factor Analysis (IFAS) and External Factor Strategy Analysis (EFAS). Strengths, Weakness, Opportunities, and Threats (SWOT) analysis is used to develop strategic alternatives and priorities. The most important internal factor is that the government is trying to maintain military security during a pandemic. The most important external factor is the relaxation of the PSBB policy from the government, so that the people of Ternate City do not experience a food crisis. The total score of the IFAS matrix is 2.9 and the EFAS matrix is 3.26. The SWOT analysis shows that the Ternate City Government needs to carry out a food diversification strategy aimed at anticipating a food crisis in Ternate City by providing local food that has a source of carbohydrates to replace the staple food, namely rice.